DETERMINING FACTORS URGE A REDENOMINATION - Handayani, Sri Wahyu (Universitas Gunadarma, 2020)
The purpose of this research was examined factors urge a redenomination. While decisions on denomination and design of currencies may seem more technical than political, a government’s control and administration of its currency and transactions within its boundaries is one of the hallmarks of the modern nation -state. With the discourse of the Indonesian central bank researchers wanted to investigate about the proper inflation level to take the redenomination. This Research aims at analysing the effect variable of inflation, exchange rate and index democracy on redenomination, and to identify the most variable than in affective redenomination. The population of this research is a country that is listed at the World Bank. Data used is secondary data. By using a purposive sampling method states that have complete data in the research consisted of 36 countries. The data is analyzed using of binary logistic regression statistical tests and with the help of SPPS V.13.0 software and Microsoft Excel 2007.The results of this research indicate that (1) exchange rate no significant effect on the decision to redenomination, (2) Form of government no significant effect on the decision to redenomination, (3) inflation significantly influence decisions redenomination of the most special is the inflation t-5. A country does not doredenomination is directly due to the socialization and factors - factors of conflictwithin a countries.